Flash advertising : flash platform development of microsites, advergames, and branded applications - Fincanon, Jason (Focal Press, 2010)
Helps you create Flash ads, microsites, advergames, and branded applications that engage consumers and demonstrate their worth to clients. This title lets you learn some of the best practices for mastering the myriad of ad specs, deadlines, quality and version control issues and creating ads that balance campaign goals with design constraints